Optimasi PVA dan HPMC dalam Masker Wajah Gel Peel Off Ekstrak Daun Beluntas (Pluchea indica L.) dengan Metode Simplex Lattice Design - Diny Puspitasari; Devina Wahyu Astaning Cristy; Fina Arista Langu (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2026)
Peel-off gel masks are widely used cosmetic skincare preparations due to their practicality, ease of removal, and non-comedogenic properties. Beluntas (Pluchea indica L.) leaf contains various bioactive compounds, particularly flavonoids, which possess antibacterial activity. This study aimed to obtain the optimum formulation of a peel-off face mask containing Beluntas leaf extract, with variations in Polivinyl alcohol (PVA) as a film-forming agent, and hydroxypropyl methylcellulose (HPMC) as a gelling agent.This experimental study employed the Simplex Lattice Design (SLD), an optimization method. Five formulations were prepared with PVA content ranging from 10-16% and HPMC concentrations from 2-4%. Each formulation was evaluated for organoleptic properties, homogeneity, pH, spreadability, drying time, adhesion, and viscosity, and the data were analyzed using Design Expert Version 13. The optimum peel-off gel mask formulation containing Beluntas leaf extract was obtained at PVA 12.92% and HPMC 3.07% with predicted spreading power 5.198, adhesion 52.910, viscosity 586.357, pH 4.626, drying time 23.502 with desirability 0.812.